1986
DOI: 10.1093/oxfordjournals.eurheartj.a062135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of supraventricular tachyarrhythmias after acute myocardial infarction

Abstract: 160 survivors of acute myocardial infarction (AMI) were evaluated to assess the clinical significance of supraventricular tachyarrhythmias (SVTA) occurring at discharge from the hospital after the acute event. All the variables considered for the study were estimated before hospital discharge; arrhythmias were quantified with a 24 h Holter ECG monitoring system. SVTA occurred in 88 patients (55%). Single or repetitive supraventricular premature beats were found in 65 (41%), paroxysmal atrial or junctional tach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Well in agreement with others, the prevalence of supra ventricular tachycardia in the present study was 14% [9], Supraventricular tachyarrhythmias occurring early after AMI has been associated with an increased risk of subse quent cardiac death [10]. It has been demonstrated to develop in the presence of large myocardial infarct and left-ventricular dysfunction [11], In the study by Berisso et al [9] of 209 consecutive patients discharged postin farction, supraventricular tachycardia, during 24-hour Holter monitoring 16 ± 3 days (mean ± SD) after the infarct, did not, in a multivariate analysis, predict 2-year cardial mortality independently from cardiac enlarge- ment on chest X-ray and left-ventricular dysfunction.…”
Section: Supraventricular Tachycardiasupporting
confidence: 94%
See 3 more Smart Citations
“…Well in agreement with others, the prevalence of supra ventricular tachycardia in the present study was 14% [9], Supraventricular tachyarrhythmias occurring early after AMI has been associated with an increased risk of subse quent cardiac death [10]. It has been demonstrated to develop in the presence of large myocardial infarct and left-ventricular dysfunction [11], In the study by Berisso et al [9] of 209 consecutive patients discharged postin farction, supraventricular tachycardia, during 24-hour Holter monitoring 16 ± 3 days (mean ± SD) after the infarct, did not, in a multivariate analysis, predict 2-year cardial mortality independently from cardiac enlarge- ment on chest X-ray and left-ventricular dysfunction.…”
Section: Supraventricular Tachycardiasupporting
confidence: 94%
“…The prevalence of atrial fibrillation in the present study was 3%, which is in accordance with other studies, documenting atrial fibrillation in 2% [9] to 16% [15] of patients postinfarction. Several studies demonstrated postinfarction atrial fibrillation to be an important pre dictor of short- [16,17] and long-term [18] survival, whereas others using multivariate analysis found oppos ing results [15,19], In a recent carefully conducted study of 295 elderly post-AMI patients, Nielsen [20] displayed, in a multivariate analysis, atrial fibrillation to convey prognostic information in the older (i.e.…”
Section: Atrial Fibrillationsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, various other potential triggers such as ischemic artery disease 15 , myocardial infarction 16 , mitral valvular stenosis 17 , smoking 18 , alcohol use 19 , caffeine use 20 , pulmonary disease 21 , and renal failure 22 have also been associated with the development of APC’s. Despite low prevalence of the majority of these risk factors in the present cohort, our study still showed a strong association of the presence of APC’s with cardiovascular and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%